EMERGING TRENDS IN INFLUENCER MARKETING: WHAT BUSINESSES NEED TO KNOW FOR FUTURE SUCCESS - Mittal, Diksha; Mathur, Shipra (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Influencer marketing has become an integral component of modern business strategies, leveraging authentic connections to bridge the gap between brands and consumers. This paper reviews the evolving trends shaping the domain, including the rise of micro and nano influencers, platform diversification, data-driven campaigns, social commerce integration, and the advent of virtual influencers. Additionally, it emphasizes the increasing importance of authenticity and the use of emerging technologies such as AR and VR in creating immersive experiences. However, the field faces challenges such as fake followers, regulatory compliance, content saturation, and ROI measurement difficulties. To address these, businesses must adopt niche community targeting, ensure transparency, invest in advanced analytics, and pursue long-term collaborations. By aligning with these trends and overcoming challenges, businesses can capitalize on influencer marketing for sustainable success.